Effect of Direct Fluorination on the Transport Properties and Swelling of Polymeric Materials: A Review; Membranes; Vol. 11, iss. 9 - Belov N. A. Nikolay Alexandrovich; Pashkevich D. S. Dmitry Stanislavovich; Alentjev (Alentiev) A. Yu. Aleksandr Yurjevich; Tressaud A. Alain (2021, 2021)
Title screen